Evaluating antipoverty transfer programmes in Latin America and sub-Saharan Africa: Better policies? Better politics? - Armando Barrientos; Juan M. Villa (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
The paper provides a comparative analysis of the incidence of evaluation methods in antipoverty transfer programmes in Latin America and sub-Saharan Africa. The paper identifies two broad explanations for the incidence of evaluation in antipoverty transfer programmes in developing countries, one emphasizing the advantages of a shift towards evidence-based development policy, and a second explanation emphasizing political factors. The paper assesses their relevance in the context of Latin American and sub-Saharan African countries with a view to throwing light on whether the evaluation of antipoverty transfer programmes will lead to an improved effectiveness of the relevant government agencies.
Keywords: D72; H43; I32; I38; 330; impact evaluation; poverty; antipoverty transfers; Latin America; sub-Saharan Africa; Armutspolitik; Wirkungsanalyse; Lateinamerika; Afrika südlich der Sahara